Removal of Lead from Aqueous Medium Using Xanthate Modified Apple Juice Residue - Bashyal, Deepak; Homagai, Puspa Lal; Ghimire, Kedar Nath (Journal of Nepal Chemical Society, 2010)
This study investigated the feasibility of chemically modified apple juice residue as a novel type of adsorbent for lead removal from aqueous medium. FTIR studies were carried out to understand the type of functional groups in unmodified and modified apple juice residue responsible for metal binding process. Equilibrium adsorption data were fitted in terms of monolayer adsorption at pH 4 by batch method. The kinetics was studied for biosorption processes and data were described by pseudo second order model. The equilibrium constant and Gibbs free energy of the adsorption at 25°C were determined. The mechanism of sorption was found to obey the ion exchange and complexation method. Keywords: Heavy metal; Biosorption; Xanthate; Iion exchange; Complexation DOI: 10.3126/jncs.v26i0.3632 Journal of Nepal Chemical Society Vol. 26, 2010 Page: 53-60